Impaired seroconversion after SARS-CoV-2 mRNA vaccines in patients with solid tumours receiving anticancer treatment - Amatu, Alessio; Pani, Arianna; Patelli, Giorgio; Gagliardi, Oscar M.; Loparco, Marina; Piscazzi, Daniele; Cassingena, Andrea; Tosi, Federica; Ghezzi, Silvia; Campisi, Daniela; Grifantini, Renata; Abrignani, Sergio; et al. (European journal of cancer (1990), 2022)
Patients with solid tumours have high COVID-19 mortality. Limited and heterogeneous data are available regarding the immunogenicity of SARS-CoV-2 mRNA vaccines in this population. This is a prospective, single-centre cohort study aiming at evaluating seroconversion in terms of anti-spike antibodies in a population of patients with solid tumours undergoing cancer therapy within 2 months before the second vaccine dose, as compared with a cohort of controls. Subjects who were not SARS-CoV-2 naïve were excluded, and 171 patients were included in the final study population (150 vaccinated with BNT162b2, 87.7%; 21 with mRNA-1273, 12.3%) and compared with 2406 controls. The median follow-up time from the second dose of vaccination was 30 days (12–42; IQR: 26–34). Most patients had metastatic disease (138, 80.7%). Seroconversion rate was significantly lower in cancer patients than in controls (94.2% versus 99.8%, p < 0.001). At univariate logistic regression analysis, Odds ratio (OR) for seroconversion was also reduced in older individuals (>70 years). A multivariate logistic model confirmed cancer as the only significant variable in impairing seroconversion (OR 0.03, p < 0.001). In the cancer population, a multivariate analysis among clinical variables, including the type of cancer treatment, showed ECOG PS > 2 as the only one of impact (OR 0.07, p = 0.012). There is a fraction of 6% of patients with solid tumours undergoing cancer treatment, mainly with poorer performance status, who fail to obtain seroconversion after SARS-CoV-2 mRNA vaccines. These patients should be considered for enhanced vaccination strategies and carefully monitored for SARS-CoV-2 infection during cancer treatment. •Cancer patients have high COVID-19 mortality and were prioritised for vaccination.•About 6% of cancer patients do not develop protective antibodies after vaccination.•Cancer in active treatment is the main factor impairing seroconversion.•Enhanced vaccination strategies warrant consideration in such a setting of care.